Pathways for the Improvement of Construction Productivity: A Perspective on the Adoption of Advanced Techniques - Pejman Ghasemi Poor Sabet; Heap-Yih Chong (Advances in Civil Engineering)
Reinventing construction is the key to improving productivity. This reinvention refers to not only inventing advanced materials and equipment but also developing new operating systems for construction projects. Inadequate application of advanced techniques impedes the operating system. Furthermore, the capabilities of advanced techniques may not cover all the areas required to meet the expected productivity level. The implications of these advanced techniques need to be reinforced by a range of productive fundamentals that remain unclarified. Further, the pathways through which these fundamentals can be aligned with the implementation of advanced techniques remain under-researched. Hence, the objectives of this research are as follows: (1) to clarify how the selected and common advanced techniques applied in this paper influence construction productivity; (2) to determine the range of productivity fundamentals required to reinforce the implementation of the advanced techniques necessary to fulfil productivity expectations; and (3) to conceptualise the integration of these productivity fundamentals with the application of advanced techniques. A scoping review of 128 articles was used to identify which fundamentals can contribute to achieving performance targets once practising these new advanced techniques. The findings reveal a comprehensive range of productivity fundamentals that are able to reinforce new advanced techniques through different pathways of their applications.